2021
DOI: 10.1111/jipb.13053
|View full text |Cite
|
Sign up to set email alerts
|

Potassium and phosphorus transport and signaling in plants

Abstract: Nitrogen (N), potassium (K), and phosphorus (P) are essential macronutrients for plant growth and development, and their availability affects crop yield. Compared with N, the relatively low availability of K and P in soils limits crop production and thus threatens food security and agricultural sustainability. Improvement of plant nutrient utilization efficiency provides a potential route to overcome the effects of K and P deficiencies. Investigation of the molecular mechanisms underlying how plants sense, abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
127
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(131 citation statements)
references
References 261 publications
(546 reference statements)
3
127
0
1
Order By: Relevance
“…Ding et al (2020) demonstrated that SPDT transporter in Arabidopsis thaliana showed a high affinity for Pi transport, as it was able to uptake Pi when injected into the Xenopus oocyte. Furthermore, its localization has been shown in the plasma membrane, while Wang et al., 2021 reported its localization in the chloroplast. These data are in agreement with reported SPDT genes which confer grain lpa phenotype (Larson et al., 2000; Liu et al., 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ding et al (2020) demonstrated that SPDT transporter in Arabidopsis thaliana showed a high affinity for Pi transport, as it was able to uptake Pi when injected into the Xenopus oocyte. Furthermore, its localization has been shown in the plasma membrane, while Wang et al., 2021 reported its localization in the chloroplast. These data are in agreement with reported SPDT genes which confer grain lpa phenotype (Larson et al., 2000; Liu et al., 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Despite of considerable progress in understanding inorganic phosphate (Pi) acquisition and the response to its starvation, no direct link is reported between these traits and grain P concentration (Baker et al., 2015; Lal et al., 2019). The mineral nutrients needed for growth and development is absorbed mainly in the root hair, which is further translocated to the different organ through the xylem (Wang et al., 2021). Recent research has shown that the transport of minerals to the grain is mediated by transporter localized at the upper nodes of the plants.…”
Section: Introductionmentioning
confidence: 99%
“…The following RT-qPCR detection also confirmed this prediction, which indicated the regulatory role of light and dark in NtCIPK23 expression ( Figure 5c). As other CIPK23 genes are proved to occupy a crucial position in nutrition, development, and stress tolerance in plants [3,4,22,38], the upstream regulation pathway of NtCIPK23 might be an interesting point to be focused on.…”
Section: Discussionmentioning
confidence: 99%
“…Inorganic Pi signaling and transport have been investigated extensively in model organisms such as A. thaliana and rice. PSR appears to involve both a long-distance, systemic response that senses cellular Pi levels, and a local, root tip inhibition response that senses extracellular Pi availability ( Wang et al, 2020d ). Sensing of cellular Pi levels relies on the PHR1-PHT1 module ( Puga et al, 2017 ; Lu et al, 2020 ), which is a multicomponent, transcriptional, and posttranscriptional regulatory network.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%